2021
DOI: 10.1038/s41593-021-00797-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep down state-active ID2/Nkx2.1 interneurons in the neocortex

Abstract: Extended Data Fig. 2 Network property statistics of DSA interneurons (A) Statistical contrast matrices (two-sided Tukey's test) for firing rates of pyramidal cells (PYR), interneurons (INT) and DSA interneurons during waking quiescence (QWake), NREM sleep, REM sleep and active behavior (Walk). (B) Same layout and statistical comparisons as in A but for the average unit CCGs as a function of brain state. (C) Pearson correlations (tested using a Student's t distribution) between average CCG responses of NREM sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 57 publications
4
76
0
Order By: Relevance
“…Nkx2.1 protein is established to be expressed in cycling-MGE progenitors around ∼ED10.5 and it is thought to be turned-off in the postnatal cortex. However, it was recently indicated that subsets of late-born axo-axonic interneurons (He et al, 2016), and subsets of NGFC interneurons (Valero et al, 2021) interneuron subsets that express Nkx2-1 gene appeared to be having increased cell recoveries in our scRNAseq assay, we examined the expression of Nkx2-1 protein in the postnatal brain with a verified antibody. First, anti-Nkx2-1 immunostaining revealed a clear expression of putative-nuclear staining in the cortex and the hippocampus, albeit at a lesser density than in the adjacent striatum on saggital sections.…”
Section: Increased Sst and Ngfc Subtypes In The Juvenile Brain Due To Loss Of Grin1mentioning
confidence: 99%
“…Nkx2.1 protein is established to be expressed in cycling-MGE progenitors around ∼ED10.5 and it is thought to be turned-off in the postnatal cortex. However, it was recently indicated that subsets of late-born axo-axonic interneurons (He et al, 2016), and subsets of NGFC interneurons (Valero et al, 2021) interneuron subsets that express Nkx2-1 gene appeared to be having increased cell recoveries in our scRNAseq assay, we examined the expression of Nkx2-1 protein in the postnatal brain with a verified antibody. First, anti-Nkx2-1 immunostaining revealed a clear expression of putative-nuclear staining in the cortex and the hippocampus, albeit at a lesser density than in the adjacent striatum on saggital sections.…”
Section: Increased Sst and Ngfc Subtypes In The Juvenile Brain Due To Loss Of Grin1mentioning
confidence: 99%
“…This enabled bilateral silicon probe implantation in the CA1 region of the hippocampus of rats ( Rogers et al, 2021 ). Reduced weight allowed us to use the same drive in mice ( Valero et al, 2021 ) and rats. (Note, that the shorter mouse microdrive is not supported anymore).…”
Section: Resultsmentioning
confidence: 99%
“…Supragranular PV + INs receive inputs from excitatory corticocortical affer-ents as well as from neighbouring pyramidal neurons (Figure 4) [149,[204][205][206], indicating that PV + INs not only provide feedforward but also feedback inhibition, preferentially targeting the proximal dendrites and the soma of pyramidal neurons. PV + INs are known to innervate Chandelier cells, VIP + , CCK + , nNOS + , and SOM + INs [194,207,208]. In contrast, SOM + INs mostly receive excitatory inputs from neighbouring pyramidal neurons and weaker inputs from thalamic and corticocortical afferents, in turn preferentially inhibiting the distal and proximal dendrites of not only pyramidal cells but also PV + , nNOS + , and VIP + INs (Figure 4) [192,193,[208][209][210][211][212][213].…”
Section: Pv + and Som + Interneuron Connectivitymentioning
confidence: 99%
“…PV + INs are known to innervate Chandelier cells, VIP + , CCK + , nNOS + , and SOM + INs [194,207,208]. In contrast, SOM + INs mostly receive excitatory inputs from neighbouring pyramidal neurons and weaker inputs from thalamic and corticocortical afferents, in turn preferentially inhibiting the distal and proximal dendrites of not only pyramidal cells but also PV + , nNOS + , and VIP + INs (Figure 4) [192,193,[208][209][210][211][212][213]. It is postulated that SOM + INs are "ideally located within the cortical circuit to modulate sensory integration" [214] Selective inactivation of PV + INs results in working memory impairments, cognitive deficits, and reduced behavioural flexibility and sociability in mice [238][239][240].…”
Section: Pv + and Som + Interneuron Connectivitymentioning
confidence: 99%